Effect Of Human Resource In Accounting Information System On Management Decision-Making In Seventh-Day Adventist Institutions In Eastern Nigeria - Okon, Edet Eyibio; Otuza, Chima Evans; Dada, Samuel O. (Advances in Social Sciences Research Journal, 2021)
The constant changes in the business environment, both domestic and international, have brought about great challenges on management of business organizations. Despite huge investments in accounting information systems, several organisations have not realized the full potential benefits of using these systems because of persistent failures. This study therefore investigated the effect of human resources in accounting information system on management decision-making in Seventh-day Adventist institutions in Eastern Nigeria Union Conference. This study adopted a cross-sectional survey research design. The population of this study was 250 accounting officers (Management, and General Administration) in the 24 entities. The sample size was total enumeration of all the 250 employees. A structured and validated questionnaire was used for data collection. The response rate was 84.4%. Data was analyzed using inferential statistics (simple linear regression analysis). The findings revealed that human resources in AIS has a positive and significant effect on management decision-making in Seventh Day Adventist Institutions in the Eastern Nigeria. Based on the findings of this study, the study recommended that institutions should give devoted attention on factors that will promote human resource development in the institutions, as this is capable of contributing positively on the management of the organization, which include informed decision-making.